Chapter Notes (2)

8 with initial condition p0 p0 the method of

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ing an initial principal of P0 . Solution: 24 2 Differential Equations We must solve (2.8) with initial condition P(0) = P0 . The method of separation of variables can be applied. Separating the variables gives dP = rdt . P Integrating both sides of the latter equation yields ln P = rt + C . Solving for P by exponentiation (see Example 2.5) we get P = Ce rt . Substituting P0 = P(0) and putting t = 0 we have P0 = Ce0 = C so the formula for the principal becomes P(t ) = P0 ert . (2.9) ! There are a number of interesting financial lessons that can be learned from (2.9). Example 2.10: a) What is the effective annual interest rate if money is compounded continuously at an annual rate r ? b) How many years are needed to double any starting principal if money earns interest at an annual rate r compounded continuously? Solution: a) By definition, the effective annual interest rate is the relative change in the principal in one year. In other words, it is the quantity P(1) − P(0) P0 er − P0 = = er − 1 . P(0) P0 When r is small (as it usually is when we are dealing with interest rates) this quantity is just slightly larger than the nominal rate r . The increase is due to the compounding. The table below shows this for some representative interest rates. For example, at 7% annual interest you would actually earn 7.25% over the course of a year. 25 2 Differential Equations r .03 .05 .07 .10 .15 Effective Annual Rate .0304 .0513 .0725 .1052 .1618 Doubling Time(years) 23.1 13.9 9.9 6.9 4.6 Table 2.1 b) We need to find how long it takes for the principal to reach double its initial amount. We must find the time t for which 2 P0 = P0 ert . Canceling the term P0 , we are left with the equation 2 = ert . To solve this equation we take the natural logarithm of both sides obtaining ln 2 = rt ln e = rt , since ln e = 1 . Denoting the solution by t2 , we have t2 = ln 2 . r (2.10) Some representative values of the doubling time are given in Table 2.1. We can derive a useful rule of th...
View Full Document

This document was uploaded on 04/06/2014.

Ask a homework question - tutors are online